2019
DOI: 10.1002/cbf.3480
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TDRG1/miR‐214‐5p axis affects preeclampsia by modulating trophoblast cells

Abstract: Because of limited treatment options, preeclampsia (PE) is the leading cause of perinatal morbidity and mortality worldwide. Recently, lncRNA TDRG1 is reported to be aberrantly down-regulated in PE placenta, and the abnormal expression of TDRG1 might play a key or partial role in PE development. In this study, we found that TDRG1 was significantly down-regulated in PE placenta compared with the normal placenta.The cell proliferation, migration, invasion, and cell cycle were explored by CCK-8, wound-healing, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…For example, lncRNA TDRG1 is abnormally downregulated in the placenta in PE, and overexpression of TDRG1 can promote the proliferation, migration, and invasion of trophoblast cells, while knockdown of TDRG1 can inhibit these processes. Studies on molecular mechanisms have shown that TDRG1 can bind to miR-214-5p, which can regulate the Jagged1 and Notch1 signaling pathways (10). In addition, lncRNAs may be used as targets for predicting and diagnosing PE in the future.…”
Section: Pathological Diagnosis Has Shown That the Occurrence Of The Disease May Be Caused By Abnormal Immune Balancementioning
confidence: 99%
“…For example, lncRNA TDRG1 is abnormally downregulated in the placenta in PE, and overexpression of TDRG1 can promote the proliferation, migration, and invasion of trophoblast cells, while knockdown of TDRG1 can inhibit these processes. Studies on molecular mechanisms have shown that TDRG1 can bind to miR-214-5p, which can regulate the Jagged1 and Notch1 signaling pathways (10). In addition, lncRNAs may be used as targets for predicting and diagnosing PE in the future.…”
Section: Pathological Diagnosis Has Shown That the Occurrence Of The Disease May Be Caused By Abnormal Immune Balancementioning
confidence: 99%
“…Previous studies have revealed that a series of lncRNAs are associated with PE by inhibiting the proliferation, migration, and invasion of trophoblast cells, promoting angiogenesis and inducing apoptosis. Among them, the expression of lncRNA Gas5 [24], lncRNA DLX6-AS1 [25], and lncRNA Linc00261 [26] is upregulated in PE, while the expression of lncRNA MALAT1 [27], lncRNA LINC00511 [28], and lncRNA TDRG1 [29] is downregulated.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation, oxidative stress, and placental trophoblast cells have all been closely linked to PE. The lack of migration and invasion of trophoblast cells has been found to contribute to inadequate remodeling of spiral arteries, the major driver of PE pathogenesis [ 15 ]. Furthermore, lncRNAs have been shown to play pivotal roles in the modulation of trophoblast cell function and the incidence of PE [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%